2017
DOI: 10.1007/s00395-017-0628-z
|View full text |Cite|
|
Sign up to set email alerts
|

Exercise-induced circulating extracellular vesicles protect against cardiac ischemia–reperfusion injury

Abstract: Extracellular vesicles (EVs) serve an import ant function as mediators of intercellular communication. Exercise is protective for the heart, although the signaling mechanisms that mediate this cardioprotection have not been fully elucidated. Here using a nano-flow cytometry, we found a rapid increase in plasma EVs in human subjects undergoing exercise stress testing. We subsequently identified that serum EVs were increased by ~1.85 fold in mice after 3-week swimming. Intramyocardial injection of equivalent qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
158
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(191 citation statements)
references
References 50 publications
7
158
0
1
Order By: Relevance
“…EVs, and in particular their composite cargos, have been consistently demonstrated to contribute to the development of cardiovascular diseases 39 . However, the therapeutic delivery of stem cell-and serum-derived EVs have been proposed as cell-free approaches for cardioprotection in models of cardiac ischemic injury 8,20 . We have recently demonstrated that the sera of healthy donors could contain pro-angiogenic EVs, which principally express endothelial and platelet markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs, and in particular their composite cargos, have been consistently demonstrated to contribute to the development of cardiovascular diseases 39 . However, the therapeutic delivery of stem cell-and serum-derived EVs have been proposed as cell-free approaches for cardioprotection in models of cardiac ischemic injury 8,20 . We have recently demonstrated that the sera of healthy donors could contain pro-angiogenic EVs, which principally express endothelial and platelet markers.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence to suggest that EVs can act as potential therapeutic, diagnostic and prognostic tools 19,20 . We have previously developed an in-vitro test of potency to predict healthy subject-derived serum-EV (sEV) pro-angiogenic properties 21 .…”
mentioning
confidence: 99%
“…Serum‐free conditioned medium was collected after treatment of ECs. Exosomes were also isolated with the ExoQuick Plasma prep and the Exosomes Precipitation Kit according to the manufacturer's instructions (System Biosciences) …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it has been found that exercise can induce cardiomyocytes to release EVs/EXs, which exert a cardioprotective function in MI. A recent study showed that the serum level of EVs was increased by about 1.85-fold in mice after 3 weeks of swimming (Bei et al, 2017). Furthermore, intramyocardial injection of EVs induced by exercise exerted additional anti-apoptotic effects on H 2 O 2 -treated H9C2 cardiomyocytes compared to exercise alone.…”
Section: Novel Secretory Mechanisms Of Exercise-induced Cardioprotectmentioning
confidence: 98%
“…Intriguingly, circulatory EVs/EXs content varies in an intensity-dependent manner in response to exercise training (Bei et al, 2017). The heart is the main endocrine organ affected during exercise, and some cardiac-derived protective factors can be induced by exercise and carried by EVs/EXs to ameliorate the pathological processes of MI (Ogawa and de Bold, 2014;Sanchis-Gomar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%